Buoy as a tool in teaching basic elements of sailing - Nikola Prlenda; Ivan Oreb; Danijela Vujčić (University of Banja Luka, Faculty of physical education and sport, 2018)
The aim of the research is to determine efficiency of buoys as a methodic tool in teaching and learning of basic elements of sailing. Analyzed sailing elements were heading up, tacking, bearing away and jibing on three different sailing positions (helm, main sail and jib). The research was carried out on the sample of 178 Kinesiology faculty students, divided into two groups (control group and experimental group). The experimental group examinees were subjected to teaching using various buoy ranges, while control group examinees were subjected to classic teaching methods (without buoy range). The teaching process was carried out during seven days period on Elan 19 sailboats. The results of descriptive statistics show higher score for examinees of experimental group in almost all elements of sailing technique, except in element tacking-jib. One-way analysis of variance showed that those differences are significant on the position helmsman in elements heading up, bearing away and jibbing, on the position mainsail, in the element heading up and also on the jib position, element heading up. Through further analysis, a discriminant analysis confirmed significant difference in the amount of acquired knowledge of sailing technique between two analyzed groups (χ2 = 47,73, p = 0,00). Finally, the authors conclude that buoy range had significant influence on the amount of acquired knowledge of sailing skills.